A multivariate receptor modeling study of air-borne particulate PAHs: Regional contributions in a roadside environment. (February 2016) - Kim, Bong Mann; Lee, Seung-Bok; Kim, Jin Young; Kim, Sunwha; Seo, Jihoon; Bae, Gwi-Nam; Lee, Ji Yi
Abstract: Understanding the geographic source contributions by particulate polycyclic aromatic hydrocarbons (PAHs) is important for the Korean peninsula due to its downwind location from source areas. Regional influence of particulate PAHs was previously identified using diagnostic ratios applied to mobile source dominated roadside sampling data (Kim et al., 2012b). However, no study has yet been conducted to quantify the regional source contributions. We applied a multivariate receptor modeling tool to identify and quantify the regional source contributions to particulate PAHs in Seoul. Sampling of roadside particulate PAHs was conducted in Seoul, Korea for four years between May 2005 and April 2009, and data analysis was performed with a new multivariate receptor model, Solver for Mixture Problem (SMP). The SMP model identified two sources, local mobile source and transported regional source, and quantified their source contributions. Analysis of the particulate PAHs data reveals three types of episodic periods: a high regional source contribution period with one case, a high mobile source contribution period with three cases, and a normal contribution period with eight cases. Four-year average particulate PAHs source contributions from the two sources are 4.6 ng m −3 and 10.7 ng m −3 for regional and mobile sources, respectively and equivalent to 30% and 70% of the total estimated contribution from each of these sources. Highlights: A new multivariate receptor model, SMP, was applied to roadside particulate PAHs. This was the first application of the SMP model to real data, and it was successful. Mobile and regional sources were identified and their contributions were estimated. The regional contribution is transported PAHs from China and/or North Korea. 4-year avg. regional source contribution is 4.6 ng m −3 (30% of total contribution).